1998
DOI: 10.1164/ajrccm.157.1.9602095
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD11b in Focal Acid–induced Pneumonia and Contralateral Lung Injury in Rats

Abstract: Neutrophil emigration in response to acid aspiration does not require the adhesion complex, CD11/ CD18. This study examined the role of CD11b/CD18 using the anti-CD11b F(ab')2, 1B6, in focal HCI-induced intracapillary neutrophil sequestration and edema formation within rat lungs, as well as the effect of pretreatment with endotoxin on this injury. The results show that at the site of aspiration pneumonia, anti-CD11b F(ab')2 did not inhibit neutrophil sequestration or edema formation, either with or without end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Binding of mediators such as chemotactic factors (e.g., the complement fragment C5a) to neutrophil receptors induces a transient resistance of the cells to deformation (27,35,60,62,69,115,289). Because neutrophils must deform to pass through the capillary bed, leukocyte activation by inflammatory mediators could effect further concentration of neutrophils at the alveolar walls (51,52,102,115,180,289). The role of mechanical factors in the initial sequestration of neutrophils in the alveolar capillaries is supported by evidence that neither L-selectin nor ␤ 2 -integrins are required (51,64,132).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Binding of mediators such as chemotactic factors (e.g., the complement fragment C5a) to neutrophil receptors induces a transient resistance of the cells to deformation (27,35,60,62,69,115,289). Because neutrophils must deform to pass through the capillary bed, leukocyte activation by inflammatory mediators could effect further concentration of neutrophils at the alveolar walls (51,52,102,115,180,289). The role of mechanical factors in the initial sequestration of neutrophils in the alveolar capillaries is supported by evidence that neither L-selectin nor ␤ 2 -integrins are required (51,64,132).…”
Section: Introductionmentioning
confidence: 99%
“…Doerschuk et al (54) demonstrated a number of years ago that this process can occur through at least two distinct pathways. One pathway reguires ␤ 2 -integrins, whereas the other does not, and the distinction depends on the stimulus (54,96,126,137,180,185,203,205,234). There is also evidence from studies in the peritoneal cavity that macrophages are essential for production of a stimulus that elicits ␤ 2 -integrin-independent neutrophil emigration (173).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the specific role of CD18 integrins in mediating PMN sequestration and directing PMN traffic into lung tissue is uncertain (5,13,25). It is known that PMN can engage CD18-dependent as well as CD18-independent pathways depending on the nature of the bacterial stimulus (10,19,20,22,26,27). Because of the complexity of PMN adhesive and migratory events in intact lungs (17,25,26), there are several questions concerning the time course of PMN sequestration and the mechanisms of increased lung microvascular permeability and edema formation induced by Gram-negative sepsis.…”
mentioning
confidence: 99%
“…Mechanisms proposed to explain this local damage include the direct corrosive effect of the aspirated gastric content (Wynne et al, 1981), the localized acute airway inflammation caused by the pepsin in gastric juice (Bathoorn et al, 2011), the localized release of bronchoactive mediators and the subsequent injury of the alveolar epithelium (Amigoni et al, 2008). Earlier studies pointed to the systemic effects predominating in the later stages (Schreiber et al, 2006); these are related mainly to inflammatory mechanisms, such as the activation of neutrophils (Motosugi et al, 1998;Weiser et al, 1997) or alveolar macrophages. Table 1 Arterial pH, Horowitz-quotient (HQ) and arterial partial CO2 pressure in Groups P10 and P4 under baseline conditions (0 min) and following aspiration.…”
Section: Discussionmentioning
confidence: 99%